EFFECT OF COMPENSATION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT ASURANSI JIWASRAYA (PERSERO) JAKARTA TIMUR - Francisco, Sonny; Saoloan, Helmut Martahi (Journal of Industrial Engineering & Management Research, 2021)
This study aims to determine the effect of Motivation and Environment Work well by Partial nor simultaneous to Performance Employee at PT Asuransi Jiwas Raya (Persero) East Jakarta. Study this is causal and quantitative associative research. The sample of this research amounted to 58 people. The determination sample was done with the method of Random Sampling. Collecting data using questionnaires and interviews, while analysis data were done with use analysis regression linear multiple. Results research at the 5% significance level shows that: 1) The results of the F test at the variable of motivation and work environment is 0.000 which means that Compensation and organizational commitment have a significant effect simultaneously on performance employees of PT Asuransi Jiwas Raya (Persero) East Jakarta. 2) Result The t-test on the Compensation variable is 2.027, with a significance value of 0.008, which means that compensation has a positive and significant effect on the performance of employees of PT Asuransi Jiwas Raya (Persero) East Jakarta.. 3) Results in t-test on organizational commitment variable is 8.411, with a significance value of 0.000 which means that organizational commitment has a positive and significant effect on employee performance of PT Asuransi Jiwas Raya (Persero) East Jakarta.. 4) The coefficient of determination test (R2 ) for the variable X 1, X 2, is 0.674 which means that the performance of employees of PT Asuransi Jiwas Raya (Persero) East Jakarta can be influenced by compensation and organizational commitment as big as 67.4%, while the remaining 32.6% is influenced by other factors that are not researched in research this.